2023
DOI: 10.3390/ijms242115872
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Treatment Induces Cardiac Dysfunction in Mice

Serena L’Abbate,
Giuseppina Nicolini,
Sabrina Marchetti
et al.

Abstract: Lithium (Li) salts are commonly used as medications for bipolar disorders. In addition to its therapeutic value, Li is also being increasingly used as a battery component in modern electronic devices. Concerns about its toxicity and negative impact on the heart have recently been raised. We investigated the effects of long-term Li treatment on the heart, liver, and kidney in mice. Sixteen C57BL/6J mice were randomly assigned to receive oral administration of Li carbonate (n = 8) or act as a control group (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This may result in arrhythmias, fetal cardiac malformations, and reduced contractile responses to adrenergic signaling ( Mehta and Vannozzi, 2017 ; Patorno et al, 2017 ; Moradi et al, 2019 ; Hamstra et al, 2023 ). Animal studies have shown that treatment with lithium carbonate at a dose of 45 mg/kg for 12 weeks causes myocardial histopathologic damage ( L'Abbate et al, 2023 ). Therefore, electrocardiograms should be monitored in patients undergoing long-term lithium therapy due to the associated prolonged QTc intervals ( Mamiya et al, 2005 ).…”
Section: Potential Side Effects and Safety Concerns With Lithiummentioning
confidence: 99%
“…This may result in arrhythmias, fetal cardiac malformations, and reduced contractile responses to adrenergic signaling ( Mehta and Vannozzi, 2017 ; Patorno et al, 2017 ; Moradi et al, 2019 ; Hamstra et al, 2023 ). Animal studies have shown that treatment with lithium carbonate at a dose of 45 mg/kg for 12 weeks causes myocardial histopathologic damage ( L'Abbate et al, 2023 ). Therefore, electrocardiograms should be monitored in patients undergoing long-term lithium therapy due to the associated prolonged QTc intervals ( Mamiya et al, 2005 ).…”
Section: Potential Side Effects and Safety Concerns With Lithiummentioning
confidence: 99%
“…Although neuroprotective/ neurotrophic effects of lithium have been demonstrated previously (Forlenza et al 2014;Roux and Dosseto 2017), there have been reports of its neurotoxicity occurring even at therapeutic doses by altering oxidative stress status in the brain (Bhalla et al 2007;Mezni et al 2017). Various studies also suggested lithium may have adverse effects such as renal impairment, cardiotoxicity, cytotoxicity in the liver, and hypothyroidism (Eskandari et al 2012;Nciri et al 2012;Shine et al 2015;Abdel Hamid et al 2020;L' Abbate et al 2023).…”
Section: Introductionmentioning
confidence: 99%